2012
DOI: 10.1111/j.1600-6143.2012.04248.x
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Kidney Graft Tumors: Results From a Multicentric Retrospective National Study

Abstract: De novo tumors in renal allografts are rare and their prevalence is underestimated. We therefore analyzed renal cell carcinomas arising in renal allografts through a retrospective French renal transplant cohort. We performed a retrospective, multicentric survey by sending questionnaires to all French kidney transplantation centers. All graft tumors diagnosed after transplantation were considered as de novo tumors. Thirty-two centers participated in this study. Seventy-nine tumors were identified among 41 806 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
75
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 54 publications
0
75
1
1
Order By: Relevance
“…Eight cases of de novo carcinomas occurred in the allograft, which is much higher to the reference study [6]. The incidence was 0.19% in this series, which is lower than our 0.78% incidence (4-fold).…”
Section: Discussioncontrasting
confidence: 51%
See 4 more Smart Citations
“…Eight cases of de novo carcinomas occurred in the allograft, which is much higher to the reference study [6]. The incidence was 0.19% in this series, which is lower than our 0.78% incidence (4-fold).…”
Section: Discussioncontrasting
confidence: 51%
“…Hetet et al [21], in a review of the literature, found that the proportion of these histological types of kidney graft cancers was similar to those in native kidney cancers, namely 20–30%. However, in our series, papillary carcinomas represented more than 50% of the tumors as previously reported [6]. …”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations